Dielectric Behaviour of Binary Polar Liquid Mixtures in Dilute Solutions of Benzene at Microwave Frequency† - Suryavanshi, B.M.; Mehrotra, S.C. (Asian Journal of Chemistry, 2010)
Dielectric relaxation behaviour of two binary systems, viz., 2- aminopropane + nitrobenzene and 2-ethoxyethanol + pyridine in dilute solutions of benzene have been studied at 9.54 GHz and at room temperature. A concentration variation method of Gopala Krishna is used to determine the experimental relaxation time (τ) of the systems. A theoretical treatment of Madan is used to determine (τ) values. A theoretical relation for determining (τ) values for non associated behaviour of binary mixture is also proposed. The results are interpreted in terms of intermolecular interactions of the relaxing griups in the mixture. The (τ) values determined from the proposed theoretical equation are consistant with the values determined from the Maddan's relation.